An Efficient Gold‐Catalyzed Domino Process for the Construction of Tetracyclic Ketoethers. Issue 44 (2nd October 2013) - Groß, Tobias; Metz, Peter
<x xml:space="preserve">Abstract</x> Au, yeah! Catalytic amounts of gold(III)chloride allow a mild and efficient oxidative domino cyclization/cycloaddition of enyne carbonyl compounds 1 and 4 to give the tetracycles 2 or 5, respectively, in the presence of pyridine N‐oxide 3 (see scheme; DCE = 1, 2‐dichloroethane).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>